14-month-old girl with prolonged fever, a desquamative rash, and a new left hemiplegia. (April 2022) - Tengbeh, George; Mohsenibod, Hadi
A young child with fever, erythematous rash, and conjunctivitis in sub-Saharan Africa is usually a case of measles. We report a-14-month-old girl with a prolonged fever, a desquamating erythematous rash, and a new left hemiplegia. This was initially diagnosed as measles but her correct final diagnosis was Kawasaki disease (KD); she very rapidly defervesced and regained normal function of her limbs after appropriate treatment. We believe this is the first reported case in Liberia of KD in a child younger than two years of age.